Intracellular Chloride Channels: Novel Biomarkers in Diseases - Gururaja Rao, Shubha; Patel, Neel J.; Singh, Harpreet (Frontiers in Physiology, 2020)
Ion channels are integral membrane proteins present on the plasma membrane as well as intracellular membranes. In the human genome, there are more than 400 known genes encoding ion channel proteins. Ion channels are known to regulate several cellular, organellar, and physiological processes. Any mutation or disruption in their function can result in pathological disorders, both common or rare. Ion channels present on the plasma membrane are widely acknowledged for their role in various biological processes, but in recent years, several studies have pointed out the importance of ion channels located in intracellular organelles. However, ion channels located in intracellular organelles are not well-understood in the context of physiological conditions, such as the generation of cellular excitability and ionic homeostasis. Due to the lack of information regarding their molecular identity and technical limitations of studying them, intracellular organelle ion channels have thus far been overlooked as potential therapeutic targets. In this review, we focus on a novel class of intracellular organelle ion channels, Chloride Intracellular Ion Channels (CLICs), mainly documented for their role in cardiovascular, neurophysiology, and tumor biology. CLICs have a single transmembrane domain, and in cells, they exist in cytosolic as well as membranous forms. They are predominantly present in intracellular organelles and have recently been shown to be localized to cardiomyocyte mitochondria as well as exosomes. In fact, a member of this family, CLIC5, is the first mitochondrial chloride channel to be identified on the molecular level in the inner mitochondrial membrane, while another member, CLIC4, is located predominantly in the outer mitochondrial membrane. In this review, we discuss this unique class of intracellular chloride channels, their role in pathologies, such as cardiovascular, cancer, and neurodegenerative diseases, and the recent developments concerning their usage as theraputic targets.